Studies on the Effect of Surface Mulch, Grass Cover and Stone Barrier on Runoff and Soil Loss under Simulated Condition for Application in Arable and Non-arable Land - Adhikari, R. N.; Rama Mohan Rao, M. S.; Husenappa, V. (Indian Forester, 2002)
The rainfall simulator is an useful tool to generate quick and satisfactory information on runoff and soil loss under different surface conditions, involving much less cost and time. The results show that sorghum stover mulch reduced runoff and soil loss considerably. It is also observed that runoff and soil loss increase with increase in degree of slope. Simple application of mulch material on the surface upto 2% slope of the field, involving almost no cost, can act as good inter-terrace soil and water conservation treatment in the black soil region, apart from improving in-situ moisture condition to increase crop production. The results show that mulched plot reduced runoff by 10 to 20% in comparison to bare plot and for individual storm, soilless is reduced from 0.5 t/ha to 0.1 t/ha (for 1% slope) and 0.8 t/ha to 0.2 t/ha (for 2% slope). Attempt has also been made to have effect on runoff and soil loss under steep slopes having stone barrier using mini rainfall simulator. It is observed that stone barrier reduced sediment density by about 50%. From discharge simulation studies it is observed that grass cover reduced runoff and the peak rate of runoff by 20 to 30%. The study shows that simple and cheap technology like surface mulch, grass cover and stone barrier can act as a good soil conservation treatment in arable and non-arable land.